Pattern of dyslipidemia among adult women with polycystic ovary syndrome in Port Harcourt, Nigeria - Green, Kinikanwo I.; Amadi, Collins (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Dyslipidemia is adjudged the most common metabolic disorder observed among women with polycystic ovary syndrome (PCOS). However, there is paucity of data to support this hypothesis in our region. Therefore, this study was structured to evaluate the pattern of dyslipidemia among women with PCOS in Port Harcourt, Nigeria. Methods: This was a retrospective study of 226 adult women with PCOS who had visited the Department of Chemical Pathology and Metabolic Medicine of a tertiary hospital in Nigeria over a 10-year period (1st January 2008 to 31st December 2017), aimed to evaluate the pattern of dyslipidemia in these women. Records on age, total cholesterol (Tc), triglycerides (Tg), high-density lipoprotein (HDL-c), and low-density lipoprotein (LDL-c) were collected and analyzed using Shapiro-Wilk, descriptive, chi-square, and Fisher’s exact statistics. Statistical significance was set at 0.05. Results: The mean age of the study population was 28.40 ± 5.75 and ranged from 18 - 42 years. Most of the study population (55.3%) were within the age group of 20 – 30 years. The most common lipid abnormalities observed among the study population were increased triglycerides (75.7%) and decreased HDL-c (61.1%) concentrations while the least was increased total cholesterol (17.7%) and LDL-c (14.5%). Dyslipidemia was observed in 80.1% of the study population and more frequent (51.9%) within the age group of 20-30 years. Conclusions: Dyslipidemia is common among young adult women with PCOS. Regular assessment for dyslipidemia should be mandatory in PCOS to mitigate the long-term consequences of its complications.